Effect of pulse width modulation-controlled LED light on the polymerization of dental composites. Issue 12 (December 2018) - Lee, Chang-Ha; Ferracane, Jack; Lee, In-Bog
Abstract: Objectives: The purpose of this study was to investigate the effects of radiant emittance and cure time of pulse width modulation (PWM)-controlled LED light on polymerization shrinkage/stress kinetics and surface hardness of dental composites. Methods: A conventional (Filtek Z250) and a bulk-fill (Filtek Bulk Fill Posterior; BFP) composite were investigated. The duty ratio (% of time the light is on) and cure time of the LED light were controlled using an Arduino UNO microcontroller (PWM) as follows: 10%/100 s, 20%/50 s, 30%/33.3 s, 40%/25 s, 50%/20 s, 100%/10 s, Increase mode (0 → 100%)/20 s, and Decrease mode (100 → 0%)/20 s at 50 Hz. The radiant exposure of each group was constant. Polymerization shrinkage/stress and Vickers hardness (HV) of composites were measured for each curing condition (n = 5). Peak shrinkage/stress rate (Rsh /Rst ) and time at peak shrinkage/stress rate (Tsh /Tst ) were also determined. Results: There was no significant difference in polymerization shrinkage or HV of composites with varying duty ratio. However, polymerization shrinkage stress, Rsh, and Rst increased and Tsh and Tst decreased with increasing duty ratio. The polymerization shrinkage stress and Rst of the Increase mode group were similar to those of the 50% duty ratio group, and the Tst of the Increase mode was delayed. The polymerization shrinkage/stress kinetics of the Decrease mode group were comparable to those of the 100% duty ratio group. Under the same light curing conditions, polymerization shrinkage/stress, Rsh, Rst, and HV of Z250 were higher than those of BFP, and the Tsh and Tst of Z250 were shorter than those of BFP. Significance: With constant radiant exposure, evaluation of polymerization shrinkage/stress kinetics and their relationships could be performed by a PWM-controlled LED curing light. These results will be helpful to determine proper curing modes with varying radiant emittance of the LED curing light for decreasing polymerization shrinkage stress of dental composites. Within the limitations of this in vitro study, when radiant exposure is constant, polymerization shrinkage stress with low initial radiant emittance can be reduced compared to that with high initial radiant emittance.